Pengaruh Ulasan OTA terhadap Service Quality, Customer Satisfaction, Customer Engagement, dan Brand Loyalty - Salsabila, Aura Nur Syifa; Millayani, Heppy (https://jurnal.binamandiri.ac.id/, 2023)
Apart from being a place to buy transportation tickets or reservations, OTAs are also used by potential customers as a place to obtain information, whether related to price, location, or the personal opinions of previous customers. This form of opinion does not only contain positive information, but also negative information which can ultimately have an influence on customer satisfaction and loyalty. This research aims to find out how the online travel agent review feature influences hotels in the City of Bandung using quantitative survey and causal methods which will be filled in by 400 respondents by determining the number of respondents using a simple random sampling technique which will later be tested using the PLS-SEM technique using software assistance. SmartPLS version 4.0. The results showed that the OTA review feature had an effect on service quality, customer satisfaction, customer engagement and customer loyalty.